HDAC6 Inhibition Promotes Transcription Factor EB Activation and Is Protective in Experimental Kidney Disease - Brijmohan, Angela S.; Batchu, Sri N.; Majumder, Syamantak; Alghamdi, Tamadher A.; Thieme, Karina; McGaugh, Sarah; Liu, Youan; Advani, Suzanne L.; Bowskill, Bridgit B.; Kabir, M. Golam; Geldenhuys, Laurette; Siddiqi, Ferhan S.; et al. (Frontiers in Pharmacology, 2018)
To contend with the deleterious effects of accumulating misfolded protein aggregates or damaged organelles cells rely on a system of quality control processes, among them the autophagy-lysosome pathway. This pathway is itself controlled by a master regulator transcription factor termed transcription factor EB (TFEB). When TFEB localizes to the cell nucleus it promotes the expression of a number of genes involved in protein clearance. Here, we set out to determine 1) whether TFEB expression is altered in chronic kidney disease (CKD); 2) whether inhibition of the cytosolic deacetylase histone deacetylase 6 (HDAC6) affects TFEB acetylation and nuclear localization; and 3) whether HDAC6 inhibition, in turn, alters the natural history of experimental CKD. TFEB mRNA and protein levels were observed to be diminished in the kidneys of humans with diabetic kidney disease, accompanied by accumulation of the protein aggregate adaptor protein p62 in tubule epithelial cells. In cultured NRK-52E cells, HDAC6 inhibition with the small molecule inhibitor Tubastatin A acetylated TFEB, increasing TFEB localization to the nucleus and attenuating cell death. In a rat model of CKD, Tubastatin A prevented the accumulation of misfolded protein aggregates in tubule epithelial cells, attenuated proteinuria progression, limited tubule cell death and diminished tubulointerstitial collagenous matrix deposition. These findings point to the common occurrence of dysregulated quality control processes in CKD and they suggest that TFEB downregulation may contribute to tubule injury in CKD. They also identify a regulatory relationship between HDAC6 and TFEB. HDAC6 inhibitors and TFEB activators both warrant further investigation as treatments for CKD.